Innovative presentations for dummies - Anthony, Ray (John Wiley and Sons, 2014)
Innovative Presentations For Dummies is a practical guide to engaging your audience with superior, creative, and ultra-compelling presentations. Using clear language and a concise style, this book goes way beyond PowerPoint to enable you to reimagine, reinvent, and remake your presentations. Learn how to stimulate, capture, and hold your audience in the palm of your hand with sound, sight, and touch, and get up to speed on the latest presentation design methods that make you a speaker who gets audiences committed and acting upon your requests. This resource delves into desktop publishing skills, online presentations, analyzing your audience, and delivers fresh, new tips, tricks, and techniques that help you present with confidence and raw power